CRISPR-on system for the activation of the endogenous human INS gene - Giménez, Carla Alejandra (2016)
Advances in the field of epigenetics have allowed the design of new therapeutic strategies to address complex diseases such as type 1 diabetes (T1D). Clustered regularly interspaced short palindromic repeats (CRISPR)-on is a novel and powerful RNA-guided transcriptional activator system that can turn on specific gene expression; however, it remains unclear whether this system can be widely used or whether its use will be restricted depending on cell types, methylation promoter statuses or the capacity to modulate chromatin state. Our results revealed that the CRISPR-on system fused with transcriptional activators (dCas9-VP160) activated endogenous human INS, which is a silenced gene with a fully methylated promoter. Similarly, we observed a synergistic effect on gene activation when multiple single guide RNAs were used, and the transcriptional activation was maintained until day 21. Regarding the epigenetic profile, the targeted promoter gene did not exhibit alteration in its methylation status but rather exhibited altered levels of H3K9ac following treatment. Importantly, we showed that dCas9-VP160 acts on patients' cells in vitro, particularly the fibroblasts of patients with T1D.